Investing in developing countries : facilities for the promotion of foreign private investment in developing countries. - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 1972)
This book give an account of incentives for the encouragement of private foreign investment in developing countries provided by the member governments of the Development Assistance Committee (DAC) of the OECD.
Includes bibliographical footnotes
hza 29/01/2019
Loans
Keywords: Investments, Foreign; Economic assistance